The learning continuum of anatomical and physiological aspects based on the difficulty levels - Hanida Listiani; Ba Subali (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Determining the level of difficulty and student development is important in the learning continuum, especially the anatomical and physiological aspects. This study aimed to collect teachers' opinions about the learning continuum of anatomical and physiological aspects based on its difficulty level. This survey research was conducted in the cities of Bantul and Yogyakarta using a questionnaire. The selection of respondents through convenience sampling, totaling 111 teachers consisting of 68 junior high school science teachers and 43 junior high school biology teachers. The data were analyzed using descriptive statistics to determine the mode of teachers’ opinions. The results of this study indicate that the learning continuum in grade X of senior high school based on difficulty level in anatomical and physiological aspects, especially multicellular and unicellular concept has not yet been formed, with the difficulty at level 4. Therefore it is necessary to the provision of subject matter is sorted from easy to difficult and adjusted to the level of development of students at each level.